PERBANDINGAN TERAPI MUSIK KLASIK DAN GENGGAM JARI TERHADAP PENURUNAN NYERI POST OPERASI APPENDIKTOMY - Rinda Anugrah Wati; Yuli Widyastuti; Nurul Istiqomah (Jurnal Surya Muda, 2020)
An appendectomy is a surgical procedure performed to cut the inflamed appendix tissue. Appendectomy can cause tissue continuity and pain in the peripheral nervous system. Non-pharmacological pain management can use classical music therapy and finger grips. A preliminary study conducted in RSUD Kab. Karanganyar found the incidence of appendectomy in July-September 2019 as many as 48 patients. To find out the comparison of classical music therapy and finger grips on the reduction of postoperative appendectomy pain, a Quasi experimental research method was used with two group comparisons pretest-posttest design, with the sampling technique is accidental sampling. From the results based on the Wilcoxon test in the classical music therapy group and finger grasping, the p value was 0.038, because the p value was <0.05, there was a difference in pain intensity before and after being given classical music therapy and finger grips. The Mann-Whitney test in the pre-test group obtained each p value of 0.650, because the p value> 0.05, it can be concluded that there is no significant difference in decreasing pain scale in postoperative appendectomy patients who are given finger grips and classical music. each of them has effectiveness in reducing post appendectomy pain. Classical music therapy and finger grips were equally effective in reducing postoperative pain in the appendectomy